Teacher Strategies in Utilizing Digital-Based Teaching Materials to Increase Student Learning Motivation at the PAUD-SDN 198 Bengkulu Utara Level - Ninuk Watini (Gayaku Publisher, 2026)
The rapid development of digital technology has transformed the educational landscape, including at the early childhood and elementary school levels. This study aims to analyze teacher strategies in utilizing digital-based teaching materials to increase student learning motivation at PAUD-SDN 198 Bengkulu Utara. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation. The results showed that teachers at PAUD-SDN 198 Bengkulu Utara implemented several key strategies: (1) selection of interactive media such as educational videos and animation-based games; (2) integration of digital materials into the Merdeka Curriculum; and (3) a collaborative approach between teachers and parents in monitoring digital use. The use of digital teaching materials significantly increased students' enthusiasm and active participation. However, challenges such as limited infrastructure and the need for increased teacher digital literacy remain. This study recommends continuous professional development for teachers and the fulfillment of digital facilities to optimize the potential of digital learning in rural areas like North Bengkulu.